2014
DOI: 10.1016/j.jpha.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carbon nanosheet from barley and its use as non-enzymatic glucose biosensor

Abstract: In this work, carbon nanosheet (CNS) based electrode was designed for electrochemical biosensing of glucose. CNS has been obtained by the pyrolysis of barley at 600–750 °C in a muffle furnace; it was then purified and functionalized. The CNS has been characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and Raman spectroscopic techniques. The electrochemical activity of CNS-based electrode was investigated by linear sweep voltammetry (LSV) and square wave voltammetry (SWV), for the oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Then, the slope was 1.32 μA⋅(mmol⋅L −1 ) −1 and the sensitivity of the V 2 O 5 /urease sensor was calculated as being 1.38 μA⋅(mmol⋅L −1 ⋅cm −2 ) −1 . The sensitivity of V 2 O 5 /urease electrode is considered low when compared with the literature [22–25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the slope was 1.32 μA⋅(mmol⋅L −1 ) −1 and the sensitivity of the V 2 O 5 /urease sensor was calculated as being 1.38 μA⋅(mmol⋅L −1 ⋅cm −2 ) −1 . The sensitivity of V 2 O 5 /urease electrode is considered low when compared with the literature [22–25].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, several materials such as, vanadium pentoxide (V 2 O 5 ) [4, 12, 13], tungsten trioxide (WO 3 ) [14–16], zinc oxide (ZnO) [17], and titanium dioxide (TiO 2 ) [18, 19] have beenproposed in the literature as material for biosensor, which may reduce costs, increase sensitivity, and possess conductive properties. V 2 O 5 is one of the oxides that has been shown to be quite promising due to its remarkable characteristics such as thermal and chemical stability, biocompatibility, and conductivity, which allows its application in multiple and different areas [22,23]. One of the best way to obtain V 2 O 5 films is via sol–gel.…”
Section: Introductionmentioning
confidence: 99%
“…1b). The extent of the ratio shifting between the bands implied possible structure defects and shifts in the grain boundaries that could affect the agglomeration of nanoparticles [29,30]. Nitrogen porosimetry was employed to investigate the materials' pore characteristics and, according to the BJH method, demonstrated that the average diameter of pores was approximately ~ 3.817 nm for both Ni@CNF and CNF (Fig.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…In order to reduce and prevent the negative effects, the diabetic patient must control their blood glucose level and maintain a daily monitor of blood glucose as well [21]. Additionally, an intimate blood glucose measurement is necessary for clinical diagnosis and treatment of diabetes mellitus [22] which makes glucose the most frequently tested, clinically-relevant analyte [23]. Thus, the continuous development of simple, accessible and effective devices to determine the glucose concentration for ordinary people is very important to contribute to fast preliminary selfdiagnosis and early treatment.…”
Section: Introductionmentioning
confidence: 99%